The Effect of Gracilaria Corticata and Scenedesmus Acuminates Extract Mixture on the Healing of Wounds Contaminated with Staphylococcus in the Rat Model - Akashe, Hooman; Jahandideh, Alireza; Khajehrahimi, Amireghbal; Kakoolaki, Shapour; Hesaraki, Saeed (Archives of Academic Emergency Medicine, 2022)
Introduction: Wound healing processes are dependent on the severity of the trauma, invasion of opportunistic microorganisms, and inflammatory, immunological, and metabolic responses. We tried to show the ability of algae to inhibit wound infection, which can lead to proper wound healing. Methods: Eighty rats were housed according to laboratory animal care protocols and divided into four groups at each operating time. Group I consisted of the non-treated animals. Group II was treated with 25% zinc oxide as a choice treatment. In the treated groups 3 and 4, an equal ratio of Gracilaria Corticata and Scenedesmus acuminate marine algae (mixed algae) was applied as 3% and 7% ointment pomade. Percentage of wound closure, number of bacteria in the wound surface, angiogenesis (Vascular endothelial growth factor; VEGF), the number of macrophages, collagen production level and transforming growth factor-beta (TGFβ), epithelialization, and fibrosis were evaluated. Results: Applying mixed algae extract 7% and zinc oxide 25% could result in a mild improvement in wound closure (df: 9, 48; F=5.97; p<0.0001). In addition, mixed algae 3%, mixed algae 7% and zinc oxide could reduce the rate of bacterial growth compared to non-treated animals (df: 3, 16; F=5.74; p=0.0007). However, these improvements do not seem to be clinically significant. Induction of angiogenesis, increase in macrophage infiltration rate, and expression of TGFβ are possible underlying mechanisms of mixed algae in accelerating wound healing process. Conclusion: The result showed that the administration of 3% and 7% mixed algae could mildly accelerate the wound healing process in a rat model of pelleted skin wound. However, it seems that its effect is not clinically significant compared to non-treated and zinc oxide treated animals.